2021
DOI: 10.3390/ani11020566
|View full text |Cite
|
Sign up to set email alerts
|

A New Limnonectes (Anura: Dicroglossidae) from Southern Thailand

Abstract: A new species in the dicroglossid frog genus Limnonectes is described from Ko Pha-ngan, Ko Samui, and Ko Lanta Yai Islands in southern Thailand. Males of Limnonectes pseudodoriae sp. nov. lack a caruncle on top of the head and very closely resemble L. doriae (Boulenger, 1887) from Myanmar and western and southern Thailand. However, the new species is distinguished from L. doriae and its congeners using an integrative taxonomic approach of morphology, mitochondrial DNA, and bioacoustics. Limnonectes pseudodoria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Based on the findings in this study, their external morphological characteristics showing depressed body shape are typical for the genus Limnonectes (Yodthong et al 2021), probably because they are dependent on their benthic feeding behaviors on which they can be observed in the bottom portion of their microhabitat (de Souza et al 2022). The coloration of the tadpoles of L. leytensis is also said to be typical for its genus (Rowley et al 2014).…”
Section: External Morphology Of Tadpolesmentioning
confidence: 63%
“…Based on the findings in this study, their external morphological characteristics showing depressed body shape are typical for the genus Limnonectes (Yodthong et al 2021), probably because they are dependent on their benthic feeding behaviors on which they can be observed in the bottom portion of their microhabitat (de Souza et al 2022). The coloration of the tadpoles of L. leytensis is also said to be typical for its genus (Rowley et al 2014).…”
Section: External Morphology Of Tadpolesmentioning
confidence: 63%
“… Ichthyophis kohtaoensis was the least found anuran, likely due to them being fossorial and nocturnal. The newly discovered Limnonectes pseudodoriae was found only near or in rocky stream bed areas as described by Yodthong et al (2021) . Though it was found in each habitat, the microhabitat is specialized for this frog as rocky stream areas are the only places they were found.…”
Section: Resultsmentioning
confidence: 88%
“…Eggs were observed on land at the edge of a pool of standing water at a leveled area of a rocky stream wash in national park forest. This newly described species has been documented on only three islands, Ko Pha-ngan, Ko Samui, and Ko Lanta ( Yodthong et al 2021 ). The individuals observed in the human-settlement area were in a flooded stream area between a house and small pond.…”
Section: Resultsmentioning
confidence: 97%
“…However, the phylogeny published by Phimmachak et al [20] indicated L. kohchangae, L. macrognathus, and L. plicatellus to be more closely related to the non-caruncle-bearing species L. doriae, L. hascheanus, and L. limborgi than to the other caruncle-bearing species (i.e., L. dabanus, L. gyldenstolpei, L. lauhachindai, L. savan). Most recently, Yodthong et al [21] described a new species related to L. doriae. Obviously, additional phylogenetic studies are needed including also nuclear DNA loci in order to resolve the relationships of the species of Limnonectes.…”
Section: Introductionmentioning
confidence: 99%